Investigation of Fresh and Hardened Behaviour of Nanostructured Concrete - Nwa-David, C. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The need for sustainable environment has triggered the deployment of supplementary cementitious materials (SCMs) which reduces the effect of carbon dioxide (CO2) emission emanating from cement production, as well as the cost implications. Cassava peel ash was adopted as a SCM but in a nanostructured form to investigate the properties of concrete. The experimental outcome of the compressive and splitting tensile strengths of nanosized cassava peel ash (NCPA)-cement concrete was presented in this paper. Materials employed for the concrete production were ordinary Portland cement, NCPA, river sand, granite chippings, and water. The compressive strength was obtained using 150 x 150 x 150 mm concrete cube specimens, while 150 x 300 mm cylindrical concrete specimens were used to assess the splitting tensile strength; both measured at 7, 14, 28, 56, 90 and 150 days of curing. The mixes were prepared for varying water cement ratios of 1.5% NCPA replacement intervals in a mix ratio of 1:1.5:3. The study revealed that the slump values increased as percentage of NCPA increased. The results showed that at a water-cement ratio of 0.75 and 19.5% NCPA replacement, the concrete attains excellent compressive strengths of 18.70 N/mm2, 22.10 N/mm2, 24.20 N/mm2, 30.10 N/mm2, 33.30 N/mm2, and 36.90 N/mm2 at 7, 14, 28, 56, 90 and 150 days respectively with 5.96 N/mm2, 7.04 N/mm2, 7.71 N/mm2, 9.60 N/mm2, 10.61 N/mm2, and 11.75 N/mm2 for splitting tensile strength. The results confirm the suitability and uniqueness of nanosization as adoption of NCPA enhances the properties of concrete in both the plastic and hardened states.